Conformational selection in the flaviviral NS2B-NS3 protease - Behnam, Mira A. M.; Klein, Christian D. (Biochimie, 2020)
The first x-ray structures of flaviviral proteases defined two conformational states, open and closed, depending on the relative position of NS2B with respect to NS3, a feature that affects the shape of the binding site. The degree of flexibility in the active site was limited to changes in the fold of NS2B rather than NS3 and an induced-fit mechanism was regarded as the main factor for ligand binding. A minor degree of conformational plasticity in NS3 is observed in the two protein chains in the asymmetric unit for the structure of Zika protease with a dipeptide boronate, synthesized in our group. We hypothesize that the NS3 fold has a crucial influence on the shape of the binding site and that a reevaluation of the induced-fit interpretation is warranted. A comparison of flaviviral protease structures identifies conformational dynamics of NS3 and their unexpected role in controlling the depth of the, otherwise shallow, active site. The structural changes of NS3 are mediated by conserved residues and reveal a subpocket, which we denote as subpocket B, extending beyond the catalytic aspartate 75 towards the allosteric binding site, providing a unique connection between the orthosteric and allosteric sites in the protease. The structural evidence supports a molecular recognition based primarily on conformational selection and population shift rather than induced-fit. Besides the implications on protease studies and drug development, this hypothesis provides an interpretation for the alternate binding modes with respect to the catalytic serine, which are observed for recently developed beta-lactam inhibitors incorporating benzyloxyphenylglycine.
Gesehen am 13.10.2020